Karyological studies on eight species of Onobrychis genus in Turkey - Sepet, Hakan; Emre, Irfan; Kiran, Yasar; Kursat, Murat; Sahin, Ahmet (Springer, 2011)
This study used karyological techniques to determine the chromosome numbers and morphology of eight species of Onobrychis L. (O. caput-galli (L.) Lam, O. aequidentata (Sibth. & Sm.) d' Urv, O. fallax Freyn & Sint. var. fallax, O. lasiostachya Boiss, O. viciifolia Scop., O. oxyodonta Boiss. subsp. armena (Bois. & Huet) Aktoklu, O. hypargyrea Boiss. and O. cappadocica Boiss.). The results of this study determined the chromosome numbers of O. cappadocica as 2n = 16; O. viciifolia as 2n = 28 and the other species as 2n = 14. The karyotypes of species consisted of median-centromeric (m) or submedian-centromeric (sm) chromosomes. However, O. oxyodonta Boiss. subsp. armena (Bois. & Huet) Aktoklu was found to have only the median-centromeric (m) chromosomes. According to the results of the present study, of the eight Onobrychis taxa, only O. hypargyrea has a pair of satellite chromosomes (sat-chromosome). Furthermore, this study detected karyotype asymmetry.
Keywords: Onobrychis; chromosome number; cytotaxonomy; karyotype